Catabolic Reductive Dehalogenase Substrate Complex Structures Underpin Rational Repurposing of Substrate Scope - Tom Halliwell; Karl Fisher; Karl A. P. Payne; Stephen E. J. Rigby; David Leys (Microorganisms, 2020)
Reductive dehalogenases are responsible for the reductive cleavage of carbon-halogen bonds during organohalide respiration. A variety of mechanisms have been proposed for these cobalamin and [4Fe-4S] containing enzymes, including organocobalt, radical, or cobalt-halide adduct based catalysis. The latter was proposed for the oxygen-tolerant Nitratireductor pacificus pht-3B catabolic reductive dehalogenase (NpRdhA). Here, we present the first substrate bound NpRdhA crystal structures, confirming a direct cobalt–halogen interaction is established and providing a rationale for substrate preference. Product formation is observed in crystallo due to X-ray photoreduction. Protein engineering enables rational alteration of substrate preference, providing a future blue print for the application of this and related enzymes in bioremediation.